DESIGN OF GREENHOUSES IN A MODERN SCADA SYSTEM - Ergashev Odiljon Alijon o‘g‘li; Juraev Asilbek Xotamjon o‘g‘li (European Science Publishing, 2024)
The purpose of this study is to design a smart green home system to help the process of vegetable growth in urban areas by utilizing SCADA and IoT technology. This system can help planting vegetables in urban areas with natural conditions that are not possible and limited land. Using the hydroponic planting method will certainly be very appropriate because it does not need soil as its growing medium. The system that we designed can control and monitor parameters that affect the development of vegetables such as temperature, humidity, nutrition, water level, light, and water use in real time.
Keywords: General information about SCADA, SCADA technology, operation process of SCADA in greenhouses, calculation of economic efficiency indicators, data analysis of air circulation, humidity control, SCADA energy efficiency.